Implementasi Kurikulum Merdeka Belajar Kampus Merdeka pada Program Studi Pendidikan Bahasa Arab - Zuhriyah, Nunik; Muhaimin, M Zunaidul; Rozani Al-Am, Maftah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This article aims to describe the implementation of the curriculum of independent learning on an independent campus with the model of development of curricula of MBKM on campus and the execution of the exchange of students and practitioners teaching the program of study of Arabic Language Education as well as discussing the two curricular options in the application of the MBKM of the study of the Arabic language education program of IAI Badrus Sholeh Kediri. Field research is field research that is used to directly review the implementation process of MBKM. This research method is carried out through qualitative descriptive research, data analysis techniques are done by exploring and analyzing the results of observations, interviews, and documentation. The findings show that: (1) the Curriculum Development Model of the Arabic Language Education study program of IAI Badrus Sholeh Kediri by adopting MBKM policy includes planning, learning process, assessment and evaluation of learning (2) implementation of the MBKM-based Arabic Language Education study program of IAI Badrus Sholeh Kediri has been carried out in two areas, namely; homeland student exchange and teaching practitioner (3) curriculum for the Arabic Language Education study program of IAI Badrus Sholeh Kediri which has two optional curricula: MBKM and regular